2017
DOI: 10.1038/srep46139
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of surgery to patients with esophageal squamous cell carcinoma

Abstract: To assess if surgery provided survival benefit to patients with esophageal squamous cell carcinoma (SCC), we performed a retrospective review of 1230 patients who were newly diagnosed with stage T2-T4 esophageal SCC from 2007 to 2014 in our hospital. There were greater than 70% of patients with age under 65 years, and more than 85% were stage T3-T4 at the time of diagnosis. The median survival time was 1.06 year (95% CI 0.99–1.1 yrs). Survival analyses showed that survival time was significantly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…The median PFS was 17 months and 3-year PFS was 32%. These results were comparable to Song et al, they reported median OS of 23 months (3-year OS=37%), and median PFS of 21 months (3-year PFS=31%), in spite of using different chemotherapy protocol in definitive chemoradiation (Paclitaxel/Oxaloplatin) [33] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The median PFS was 17 months and 3-year PFS was 32%. These results were comparable to Song et al, they reported median OS of 23 months (3-year OS=37%), and median PFS of 21 months (3-year PFS=31%), in spite of using different chemotherapy protocol in definitive chemoradiation (Paclitaxel/Oxaloplatin) [33] .…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the other prognostic factors affecting the survival; the disease stage was a significant factor affecting both OS and PFS, our results were consistent with Haisley et al, [25] who reported a significant impact of disease stage on survival rates. Another investigators were reported that clinical T4 disease and absence of pathologic complete response were independently associated with inferior overall and disease-free survival [33] .…”
Section: Discussionmentioning
confidence: 98%
“…Despite improvements in diagnosis and treatments of esophageal cancer patients, overall 5-year survival rates were still very low (-40%) (1,2). Esophagectomy is the standard strategy for resectable EC.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal carcinoma (EC) is an aggressive tumor entity with a high rate of local recurrences and distant metastases, even after curative R0 resection in patients without lymph node metastases defined by routine histopathological examination (pN0) [1][2][3]. Although postoperative morbidity and mortality rates have declined over the past decade, survival rates remain poor with a median survival of 16-20 months even after curative treatment [4,5]. Metastatic lymph node invasion is still the strongest prognostic factor for overall survival and tumor-related death following esophagectomy [6].…”
Section: Introductionmentioning
confidence: 99%